Pakistan : 2021 Article IV Consultation, Sixth Review Under the Extended Arrangement Under the Extended Fund Facility, and Requests for Waivers of Applicability and Nonobservance of Performance Criteria and Rephasing of Access-Press Release; Staff Report; and Statement by the Executive Director for Pakistan. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2022)
Economic activity has rebounded strongly on the back of waning COVID-19 infections and expansionary fiscal and monetary policies. However, strong import growth-fueled by the macroeconomic policy mix, higher international commodity prices, and credit growth-have led to a marked deterioration of the external position. The current account deficit has widened, the rupee depreciated markedly, and inflation remains persistently high.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy